PP.02.27: ARTERIAL BLOOD PRESSURE BEHAVIOUR AFTER AEROBIC EXERCISE IN HYPERTENSE INDIVIDUALS THAT WERE UNDERGONE A CARDIOVASCULAR REHABILITATION PROGRAM MME. (June 2015) - Bachur, C.; Bachur, J.A.; Veiga, E.V.; Silva, P.C.S.; Machado, J.P.
Abstract : Objective: To assess which type of exercise is more effective to reach the hypotensive effect. Design and method: This study was approved by the Ethics Committee of the University of France, No. 077/06 protocol. This study is a comparative, cross-sectional, exploratory, descriptive quantitative approach. All participants underwent single session of aerobic exercise on a stationary bicycle and another single session in a therapeutic pool. Blood pressure measurements were performed at rest, 5, 15 and 30 minutes after starting the session, and 10 minutes after the session ends. For statistical analysis, the data of systolic and diastolic blood pressure were compared by analysis of variance ANOVA and the Student t test was used to locate the significant differences considering p < 0.05. Results: 30 participants, patients with Hypertension, with an average age of 55.69 + 3.45 years, weight 84.1 + 4.12 kg; 163.2 + 2.31 cm height; BMI 31.74 + 1.19 kg / cm2. Systolic blood pressure measured during this post-exercise protocol on the exercise bike remained significantly lower than the value of systolic blood pressure pre-exercise (130 vs 120 + 4.71 mmHg, p = 0.05), while diastolic blood pressure did not identify significant interaction in the post in relation to pre-exercise period (80 vs 80 + 4.7 mmHg, p = 0.18). There was no statistical difference in pre and post-exercise both SBP (120 x 120 + 4.71 mmHg) and DBP (80 x 70 + 14.14 mmHg, p = 0.18) for the years in therapy pool. Conclusions: A single session of aerobic exercise performed on the exercise bike in hypertensive individuals was sufficient to cause a significant reduction in systolic blood pressure after exercise, which is the most effective modality compared with exercise performed in the therapeutic pool.